Pengaruh E-Commerce Tokopedia Dan Marketplace Facebook Terhadap Media Jual-Beli Digital - Kristian Andrew Wahyudi (Jurnal Manuhara : Pusat Penelitian Ilmu Manajemen dan Bisnis, 2024)
This research aims to learn more about "the impact of Tokopedia online store and Facebook marketplace on digital buying and selling media", answering the main problem at hand, namely how the impact of Tokopedia online store and Facebook marketplace on digital buying and selling media. The main idea of this research is how technological advances can be utilized to increase the profitability of MSMEs. The purpose of this research is to find out how the impact of Tokopedia e-commerce and Facebook marketplace on the sales of products owned by MSME players will increase. The method used in this research is a quantitative descriptive method that aims to determine the relationship between different variables. At the same time, this research should be supported by questionnaires and documentary studies. The basic population of this research is Tokopedia and Facebook Marketplace users. The least number of samples was taken from the SEM analysis, so the technique used was probability sampling with simple random sampling technique. The conclusion of this study is how the use of Tokopedia and Facebook Marketplace affects the level of product sales.